2022
DOI: 10.1155/2022/3245206
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Autonomy in Guiding Decisions around the Feedback of Individual Genetic Research Results from Genomics Research: Expectations of and Preferences from Researchers in Botswana

Abstract: Background. The Human Health and Heredity (H3Africa) Consortium continues to generate large amounts of genomic data leading to new insights into health and disease among African populations. This has however generated debate among stakeholders involved in developing, implementing, and applying ethical standards and policies for the return of individual genetic research results. The key questions are about when results must, should, may, or must not be returned and by whom. This study aimed to explore the views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The language and the methods used to communicate were considered not fitting for the families. Similar studies done in Africa for genomic research reported similar findings (Kasule et al, 2022). The current practice is to provide results for SCD at the clinic and for the SCT, results are provided through telephone.…”
Section: Discussionsupporting
confidence: 84%
“…The language and the methods used to communicate were considered not fitting for the families. Similar studies done in Africa for genomic research reported similar findings (Kasule et al, 2022). The current practice is to provide results for SCD at the clinic and for the SCT, results are provided through telephone.…”
Section: Discussionsupporting
confidence: 84%
“…Respondents also suggested the need to engage genetic counselors when determining an appropriate communication method of returning these results to communities. Currently, there are few genetic counselors in some sub-Saharan African countries while others do not have any genetic cousellor, yet genomic research in rapidly increasing in Sub-Saharan Africa [65,66]. Genetic counselors are skilled professionals in providing scientific information about genomic and genetics and social support to participants involved in genomic research.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural competency in mental health means the ability to engage with communities from different cultural backgrounds efficiently and in an appropriate and relevant manner. A clinician’s understanding of the socio-cultural factors balanced with the relevant medical issues is important to empowering patients to make sense of information shared on genetic aspects of the causes of schizophrenia ( 7 , 17 ).…”
Section: The African Context Of Ethical Principles In Genetic Counsel...mentioning
confidence: 99%